A Tailored Approach to Launch Community Coalitions Focused on Achieving Structural Changes: Lessons Learned From a HIV Prevention Mobilization Study. (November 2015) - Chutuape, Kate S.; Willard, Nancy; Walker, Bendu C.; Boyer, Cherrie B.; Ellen, Jonathan
Abstract : Public health HIV prevention efforts have begun to focus on addressing social and structural factors contributing to HIV risk, such as unstable housing, unemployment, and access to health care. With a limited body of evidence-based structural interventions for HIV, communities tasked with developing structural changes need a defined process to clarify their purpose and goals. This article describes the adaptations made to a coalition development model with the purpose of improving the start-up phase for a second group of coalitions. Modifications focused on preparing coalitions to more efficiently apply structural change concepts to their strategic planning activities, create more objectives that met study goals, and enhance coalition procedures such as building distributed coalition leadership to better support the mobilization process. We report on primary modifications to the process, findings for the coalitions, and recommendations for public health practitioners who are seeking to start a similar coalition. Abstract : This article describes a tailored approach for launching community coalitions seeking to build a structural change agenda to address a challenging public health issue such as HIV/AIDS.